The Transnational Activist Transformations and Comparisons from the Anglo-World since the Nineteenth Century (Palgrave Studies in the History of Social Movements, 2018)
This book provides the first historical and comparative study of the 'transnational activist'. A range of important recent scholarship has considered the rise of global social movements, the presence of transnational networks, and the transfer or diffusion of political techniques. Much of this writing has registered the pivotal role of 'transnational' or 'global' activists. However, if the significance of the 'transnational activist' is now routinely acknowledged, then the history of this actor is still something of a mystery. Most commentators have associated the figure with contemporary history. Hence much of the debate around 'transnational activism' is ahistorical, and claims for novelty are not often based on developed historical comparison. As this volume argues, it is possible to identify the 'transnational activist' in earlier decades and even centuries. But when did this figure first appear? What are the historical conditions that nurtured its emergence? What are the principal moments in the development of the transnational activist? And do the transnational activists of the Internet age differ in number or nature from those of earlier years? These historical questions will be at the heart of this volume.